1997
DOI: 10.1017/s0022112097007428
|View full text |Cite
|
Sign up to set email alerts
|

A method for computing unsteady fully nonlinear interfacial waves

Abstract: We derive a time-stepping method for unsteady fully nonlinear two-dimensional motion of a two-layer fluid. Essential parts of the method are: use of Taylor series expansions of the prognostic equations, application of spatial finite difference formulae of high order, and application of Cauchy's theorem to solve the Laplace equation, where the latter is found to be advantageous in avoiding instability. The method is computationally very efficient. The model is applied to investigate unsteady … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 38 publications
9
48
0
Order By: Relevance
“…Although (3.24) has a similar form to that of the solitary wave of depression summarized in Grue et al [25], it is nevertheless a different solution, since in the present situation, the lowest fluid is stationary. The result (3.21)-(3.23) thus represents the complete solitary wave solution in the weakly nonlinear analysis.…”
Section: Weakly Nonlinear Theorymentioning
confidence: 61%
See 1 more Smart Citation
“…Although (3.24) has a similar form to that of the solitary wave of depression summarized in Grue et al [25], it is nevertheless a different solution, since in the present situation, the lowest fluid is stationary. The result (3.21)-(3.23) thus represents the complete solitary wave solution in the weakly nonlinear analysis.…”
Section: Weakly Nonlinear Theorymentioning
confidence: 61%
“…This is discussed in detail by Whitham [24], for example. (A summary of the various solitary wave theories is also given in the paper by Grue et al [25].) In terms of the original variables obtained from (3.1) and (3.10), the lower and upper interfaces are predicted by this weakly nonlinear analysis to have the profiles…”
Section: Weakly Nonlinear Theorymentioning
confidence: 99%
“…In contrast, for the cases in which the cubic nonlinearity became important, the agreement between measurements and the numerical solutions was improved, showing a progression from undular bores upstream, to monotonic bores in the transcritical regime, to steady flow over the topography for supercritical flows (see Figure 6). Grue et al (1997) developed a numerical scheme for fully nonlinear two-layer systems and found very good agreement with the measurements of Melville & Helfrich (1987). They concluded that weakly nonlinear theories may have quite limited application in modeling unsteady transcritical two-layer flows, and that fully nonlinear methods are generally required.…”
Section: Generationmentioning
confidence: 87%
“…Here, the interest is in the behaviour of so-called internal solitary waves, which are common in coastal and marginal seas (e.g., Vlasenko et al (2005) and Ostrovsky and Stepanyants (1989)) and the atmospheric boundary layer (e.g., Christie (1989)). Theoretical models (e.g., Grue et al (1997)) have relied heavily on experimental verification (e.g., Grue et al (1999)). However, to date such models have assumed simple two-layer stratifications separated by a sharp interface.…”
Section: Introductionmentioning
confidence: 99%